Prevalence of mesiodens in orthodontic patients with deciduous and mixed dentition and its association with other dental anomalies - Lara,Tulio Silva (2013)
OBJECTIVE: To determine the prevalence of mesiodens in deciduous and mixed dentitions and its association with other dental anomalies. MATERIAL AND METHODS: Panoramic radiographs of 1,995 orthodontic patients were analyzed retrospectively, obtaining a final sample of 30 patients with mesiodens. The following aspects were analyzed: gender ; number of mesiodens; proportion between erupted and non-erupted mesiodens; initial position of the supernumerary tooth; related complications; treatment plan accomplished; and associated dental anomalies. The frequency of dental anomalies in the sample was compared to reference values for the general population using the chi-square test (c²), with a significance level set at 5%. RESULTS: The prevalence of mesiodens was 1.5% more common among males (1.5:1). Most of the mesiodens were non-erupted (75%) and in a vertical position, facing the oral cavity. Extraction of the mesiodens was the most common treatment. The main complications associated with mesiodens were: delayed eruption of permanent incisors (34.28%) and midline diastema (28.57%). From all the dental anomalies analyzed, only the prevalence of maxillary lateral incisor agenesis was higher in comparison to the general population. CONCLUSION: There was a low prevalence of mesiodens (1.5%) in deciduous and mixed dentition and the condition was not associated with other dental anomalies, except for the maxillary lateral incisor agenesis.